Matthew Paris’s manuscripts: working books and artefacts in medieval and modern collections - Dunning, ANJ (Cambridge University Press, 2023)
The illustrated histories of Matthew Paris can appear almost untouched by the passage of time. It not at once clear that the custodians of Matthew’s books have altered them for reading, display, and conservation. These include the monks of St Albans; connoisseurs such as Matthew Parker (1504–75) and Robert Cotton (1571–1631) who acquired manuscripts following the dissolution of the monasteries; and institutional libraries, who continue to conserve and present these objects in new ways.